A theoretical approach to energy requirements in guinea pigs (Cavia porcellus) - Armando Tapie, William (2024)
Introduction. In some countries of the Andean region, interest in guinea pig (Cavia porcellus) breeding is growing due to the potential of this species’ meat to contribute to food security. Genetic improvement in guinea pigs has resulted in animals with high productive yields. However, these advancements have not been accompanied by studies on the net energy requirements of guinea pigs. Objective. To perform a theoretical estimation of the energy requirements for maintenance and weight gain in guinea pigs. Development. Based on bibliographic information regarding of the energy of rabbits and guinea pigs, an approximate calculation of energy requirements for weight gain and maintenance in guinea pigs was established. For this purpose, an animal with an initial weight of 0.3 kg and a final weight of 1.2 kg, with an average gain of 13 g/day, was considered. It was found that energy studies in guinea pigs for meat production are mostly expressed in energy densities, primarily in digestible energy (DE), whose values were between 2700 and 3000 kcal/kg of dry matter, and to a lesser extent of metabolizable energy. According to theoretical calculations, for an animal with an average live weight of 0.75 kg, the DE requirements for maintenance and weight gain were 92.8 and 49.34 kcal/day, respectively. With a diet providing 3000 kcal of DE in the feed, the animal must consume 47.38 g of dry matter to meet its total requirements. Conclusion. The energy requirements derived from theoretical calculations were biological consistent for meat production guinea pigs.